Application of failure model and effect analysis in nursing care for patients who have undergone endoscopic sub-mucosal dissection - Ying Liu; Kun-Kun Li; Lu Li; Ning Chang; Xiang-Ling Lun; Zhi-Hua Guan (BMC Nursing)
Abstract Objective The objective of this study is to investigate the effect after the application of Failure Model and Effect Analysis (FMEA) in nursing care for patients who have undergone endoscopic submucosal dissection (ESD). Methods A cohort of 40 patients who underwent ESD between July and September 2023 were selected as the control group, while 42 patients who underwent ESD between October 2023 and June 2024 after implementing FMEA were selected as the observation group. A multidisciplinary team was established based on the FMEA model to analyze and create a nursing flowchart. The 3 primary processes and 13 sub-processes were thoroughly analyzed and assessed to identify potential failure models, possible causes of failure, and consequences for each sub-process. Risk Priority Numbers (RPNs) were calculated to determine priority failure models, including medication and item preparation, specimen collection, equipment/instrument/accessory preparation, and nursing coordination. Corresponding improvement measures were formulated and implemented followed by a subsequent analysis of the effects. Results After implementing the improvement measures, there was a significant decrease in RPNs in the observation group when compared with the control group. A statistical significance was observed in context of medication and item preparation (P < 0.001), specimen collection (P < 0.001), equipment/instrument/accessory preparation (P < 0.001), and nursing coordination (P < 0.001). Conclusion The application of the FMEA model can effectively facilitate early nursing interventions for identified risks in patient who have undergone ESD. By instituting suitable corrective measures for aspects deemed high-risk, this approach significantly diminishes surgical nursing hazards, enhances the quality of nursing care, and guarantees patient safety.